Leprosy control strategies and the integration of health services: an international perspective - Visschedijk Jan; Engelhard Anrik; Lever Peter; Grossi Maria Aparecida de Faria; Feenstra Pieter (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2003)
Integration of leprosy services into the general health services is regarded as the core strategy to ensure that leprosy control remains cost-effective and equitable, and, thus, sustainable in the coming years. In this article an extensive review is presented of the integration of leprosy services into the general health services. After the rationale of integration is discussed, the article highlights several recent developments within leprosy control and the health sector that are in support of the integration process. An overview is presented of recent experiences in countries that have already embarked on the integration process. Based on these experiences important lessons can be learned and incorporated into a model for the process of integration. This model, which is presented at the end of the article, will assist countries to successfully integrate leprosy services into the general health services.